Developing Strategies to Help Bee Colony Resilience in Changing Environments - Isabelle Dequenne; Jean-Michel Philippart de Foy; Patrice D. Cani (Animals, 2022)
Climate change, loss of plant biodiversity, burdens caused by new pathogens, predators, and toxins due to human disturbance and activity are significant causes of the loss of bee colonies and wild bees. The aim of this review is to highlight some possible strategies that could help develop bee resilience in facing their changing environments. Scientists underline the importance of the links between nutrition, microbiota, and immune and neuroendocrine stress resistance of bees. Nutrition with special care for plant-derived molecules may play a major role in bee colony health. Studies have highlighted the importance of pollen, essential oils, plant resins, and leaves or fungi as sources of fundamental nutrients for the development and longevity of a honeybee colony. The microbiota is also considered as a key factor in bee physiology and a cornerstone between nutrition, metabolism, growth, health, and pathogen resistance. Another stressor is the varroa mite parasite. This parasite is a major concern for beekeepers and needs specific strategies to reduce its severe impact on honeybees. Here we discuss how helping bees to thrive, especially through changing environments, is of great concern for beekeepers and scientists.